PENGARUH METODE BERMAIN DENGAN BAHAN DAUR ULANG TERHADAP KEMAMPUAN BERHITUNG ANAK KELOMPOK B USIA 5-6 TAHUN DI TK INSAN PRESTASI - Dewi, Kadek Puspa (Education For All, 2023)
ABSTRACT The aim of the research was to find out whether there was a significant effect of the method of playing with recycled materials on the numeracy skills of children in group B (aged 5-6 years) at Insan Selamat Kindergarten. This research uses a quantitative approach using an experimental method with a pre-experimental research design. One-group pre-test post-test type design. The total sample was 26 children in group B of Kindergarten Insan Selamat. The data collection technique in this research is through participant observation and documentation in the form of photos of activities and daily learning implementation plans. Shows the amount of data processing using Wilcoxon signed level test data analysis. The results of data analysis obtained a value of Tcount <Ttable (0 < 25) and Ha was accepted. Shows that there was an increase from 27.5% during the pretest to 43.49% during the posttest. Based on the data analysis, there was a significant influence between playing methods with recycled materials on children's numeracy skills. Keywords: Play Method, Recycled materials, Counting Ability, Children Aged 5-6 Years.